The Impact of the Sustainable Development Agenda on the Transformation of National Policies of Commodity Producing Countries - Yakovlev, Igor A.; Kabir, Lyudmila S.; Nikulina, Svetlana I.; Rakov, Ivan D. (Economy of Regions, 2020)
In 2015, as a response to global challenges, the members of the United Nations (UN) designed the Sustainable Development Goals they intend to achieve by 2030. The transition to a green economy is at the core of the global sustainable development agenda. Such an approach includes the introduction of sustainable production and consumption patterns, increased use of renewable energy sources, and carbon footprint reduction in production chains. In particular, the countries that export fuel and energy resources are under pressure due to the plans to stop using hydrocarbons as a fuel source. Subsequently, a new technological paradigm will put additional pressure on the countries that export mineral resources. Thus, it is appropriate to examine how commodity producing countries integrate the principles of sustainable development in national policies. We analysed the countries that are largely dependent on the export of fuel and energy resources as well as the countries that export mineral resources. Then, we assessed the participation of these countries in key international initiatives for sustainable development. Finally, we summarised and systematised the approaches of the examined countries to introduce sustainable development principles into national strategies and policies. Examination of the international experience allows making the following conclusions. Commodity producing countries consider the global sustainable development agenda as an opportunity to improve the national economy and implement the reforms necessary for further development. In this case, the global agenda is an additional argument to substantiate the necessity of reforms for the national elite. In the field of sustainable development, there is a trend towards strengthening the regulatory role of the state, which combines direct control measures and measures aimed at the establishment of the green national economy.